Analysis of the Need for Innovative Use of Google Sites in Teaching Inland and Marine Geography Based on Student Characteristics - Aulia Amatullah; Listyo Yudha Irawan; Yusuf Suharto; Hidayah Eka Fitriyah (IAIN Madura, 2026)
The development of digital technology in education is important to help students overcome difficulties in learning geography, especially abstract topics such as the hydrological cycle and marine water movements. This study aimed to develop interactive, contextual, and student-centered learning media using Google Sites for geography learning. The research used a Research and Development (R&D) approach with the 4D model, consisting of Define, Design, Development, and Dissemination stages. The study involved 35 students of class X at SMAN 1 Tumpang. Data were collected through classroom observations, questionnaires, and interviews distributed using Google Forms and analyzed descriptively. The results showed that students needed innovative digital learning media. About 68.6% of students preferred learning media containing contextual concepts and real-life examples, while 17.1% preferred collaborative learning features. In addition, 5.7% expected informative maps, and 8.6% wanted interactive quizzes. These findings indicate that Google Sites-based media can support effective and innovative geography learning.